Electrolyzed water for sanitation in meat patties factory: a case study - Khalid, Nurul Izzah; Ab Aziz, Norashikin; Noh, Teh Ubaidah (Elsevier, 2024)
Daily sanitation processes are imperative for small–medium enterprises (SMEs) operating in meat patties factories, as they ensure the safety of finished products and minimize contamination risks. In this study, the focus was specifically on meat patties Factory X in Malaysia. The aim was to propose a green sanitation program aimed at reducing costs associated with daily sanitation processes. The proposed program integrates various cleaning tools, including industrial cleaning brushes and a portable electrolysis sanitation unit developed using the Theory of Inventive Problem Solving (TRIZ) method for conceptual design. The portable electrolysis sanitation unit provided continuous high–speed water flow (up to 10 L/min) at temperatures of up to 80 °C and contained both alkaline and acidic electrolyzed water (AlEW and AcEW), which can serve as alternatives to expensive commercial cleaning solutions. The study envisioned efficient cleaning and disinfection processes by harnessing the benefits of AlEW and AcEW while upholding food safety standards and quality and significantly curbing operational costs. This approach also aligns with contemporary sustainability goals by promoting an environmentally friendly green sanitation solution. © 2023 Elsevier Ltd